Morphological ontogeny, distribution and ecology of Arthrodamaeus italicus and A. mongolicus (Acari: Oribatida: Gymnodamaeidae). Issue 3 (2nd April 2016) - Seniczak, Stanisław; Seniczak, Anna; Kaczmarek, Sławomir
ABSTRACT: The morphological ontogeny of Arthrodamaeus italicus (Berlese, 1916) and A. mongolicus Bayartogtokh & Weigmann, 2005 is investigated for the first time. The juveniles of these species have long legs and are covered with granular cerotegument, which is typical of Gymnodamaeidae, but A. italicus has smooth cuticle on the gastronotum and setiform setae, whereas A. mongolicus has plicate cuticle and leaf-like setae. The larvae of both species lack seta h 3, but the former species also lacks paraproctal setae. The nymphs of both species lack gastronotal setae la, lm and the d -series and carry the exuvial scalps of previous instars, which is typical of eupheredermous Brachypylina (Circumdehiscentiae). Arthrodamaeus italicus uses the long seta c 3 and medium sized and curved setae c 1, lp and h 1 to protect these scalps against loss, whereas A. mongolicus uses the plicate cuticle. However, these four setae only weakly connect the exuvial scalps to the gastronotum of A. italicus, and the nymphs usually lose these scalps during extraction in alcohol, whereas the plicate cuticle firmly connect these scalps to the gastronotum of A. mongolicus and the nymphs bear them. The nymphs of these species have a well-developed posterior excrescence, with two pairs of setae ( h 1 and p 1 ), also typical for Gymnodamaeidae, and probably is of defence importance. Arthrodamaeus italicus is a European centromeridional species, whereas A. mongolicus is known only from Mongolia. The former species is more abundant in cypress litter, but was also found in pine, yew and bush litter, whereas the latter species lives in moss and bush litter. In A. italicus, the juveniles usually dominated, whereas in A. mongolicus, the juveniles were as abundant as the adults.